Complete mitochondrial genome of oriental pratincole Glareola maldivarum (Charadriiformes: Glareolidae) and its phylogenetic relationship. Issue 7 (3rd July 2022) - Peng, Caichun; Gou, Xue; Li, Shize; Wang, Cheng; Mu, Lang; Yang, Shuhan; Hu, Canshi; Zhang, Mingming; Su, Haijun
Abstract: Oriental Pratincole Glareola maldivarum is a widely distributed water bird species of the Charadriiformes group across Eurasia. In this study, we reveal the mitochondrial genome sequence of the Oriental Pratincole for the first time. The length of the mitochondrial genome is 18, 422 bp and contains 2 ribosomal RNA genes, 13 protein coding genes, 22 transfer RNA genes, and 2 D-loop sequences. We further provide a phylogenetic tree showing relationships among Oriental Pratincole and other Charadriiformes species.